Association between CYP2B6 c.516G >T variant and acute leukaemia: A protocol for systematic review and meta-analysis. Issue 32 (13th August 2021) - Xiong, Xuan; Yu, Dongke; Gao, Qiaoyue; Zhang, Yuan; Yin, Qinan; Chen, Xiaotao; Xiao, Hongtao; Tong, Rongsheng
Abstract: Background: Acute leukemia (AL) is a kind of malignant tumor of hematopoietic system. A number of studies have suggested that Single Nucleotide Polymorphisms are significantly associated with risk of AL. Present study performs meta-analysis to evaluate the association between CYP2B6 c.516G>T variant and AL risk. Methods: Databases including PubMed, EMBASE, Chinese National Knowledge Infrastructure (CNKI), and Wanfang were searched for literatures to September 30, 2019, both in English and Chinese. Relative risk and its 95% confidence intervals were used to assess the associations. Statistical analyses of this meta-analysis were conducted by using STATA 13.0. software. Results: A total of 7 studies, including 1038 cases and 1648 controls, were analyzed. Our results indicated that CYP2B6 c.516G>T variant was significantly related to an increased the risk of AL under dominant model, recessive model, homozygote model, and allelic model. In addition, subgroup analyses were also performed by disease classification, country, and study design. No significant associations were obtained between CYP2B6 c.516G>T variant and the risk of AL under the recessive model in the design of hospital-based (relative risk = 0.98; 95% confidence interval: 0.95–1.01; P = 0.118). Conclusion: Our meta-analysis indicated that the CYP2B6 variant is significantly associated with AL risk, in which CYP2B6 c.516G>T is related to an increased risk of AL.